Comparação entre potenciais evocados auditivos de estado estável, potenciais evocados auditivos de tronco encefálico por clique e avaliação comportamental em uma população pediátrica - Ana Carolina Andrade Valadares (2023)
ABSTRACT Introduction: Hearing is important to children’s adequate development of oral language, thus requiring precise and timely audiological diagnosis in early childhood. Hence, it is essential to study in-depth electrophysiological hearing examinations and ensure their reliability to predict psychoacoustic thresholds. Objective: The objective of this study was to compare click-evoked auditory brainstem response (ABR), auditory steady-state response (ASSR), and behavioral examinations. Methods: This cross-sectional descriptive observational study was conducted at the Hearing Healthcare Service at São Geraldo Hospital. The sample comprised 16 children aged 3 months to 5 years and 1 month, totaling 31 ears. The procedures used in the research were medical history survey, otoscopy, tympanometry, ABR, ASSR, and behavioral examinations. The descriptive data analysis was based on absolute and relative frequencies of categorical variables and measures of central tendency and variability of continuous variables. Auditory examination results were correlated using the Spearman test. The significance level was set at 5%; significant correlations were those with a moderate or strong correlation and p < 0.05. Results: The sample comprised 11 (68.75%) boys and five (31.25%) girls, with a mean age of 2.5 years and a standard deviation of 1.3. Of the 31 ears assessed in the research – i.e., in 15 of the 16 diagnosed children –, five ears had mild, three had moderate, and 11 had severe/profound sensorineural hearing loss, whereas the other 12 were normal hearing ears. ASSR was moderately correlated with behavioral assessment at 2000 and 4000 Hz. The analysis of the difference between ASSR and behavioral assessment showed a variation of about -6 to 2 dB, depending on the frequency, with standard deviations ranging from 19 to 26 dB. ASSR was moderately correlated with ABR at 2000 Hz and strongly correlated at 4000 Hz. The mean ASSR thresholds in 2000 and 4000 Hz were moderately correlated with ABR thresholds. There was no statistically significant correlation between ABR and behavioral assessments. Conclusion: The data analysis on electrophysiological examinations in the research population led to the conclusion that ASSR is moderately correlated with behavioral assessments and moderately and strongly correlated with click-ABR. The examinations proved to be effective for audiological diagnosis, further contributing to cross-checking. Keywords: Hearing; Child; Diagnosis; Evoked Potentials, Auditory; Audiometry.